Rola posłowia w przekładzie Herztier Herty Müller na język czeski - Altmann, Jakob (Przekłady Literatur Słowiańskich, 2017)
The Role of Afterword in the Czech Translation of Herta Müller’s Herztier This article deals with the relevance of paratexts in translation based on the example of the afterword in the Czech translation of Herta Müller’s novel Herztier [The Land of Green Plums], titled Srdce bestie and written by Radka Denemarková, a writer and translator famous not only in her homeland. Firstly, the elucidation analyses the essentials of paratext as such, pointing out that translation is a specific type of paratext itself, not to mention the translator’s afterword which, in turn, constitutes — from the point of view of translation — another paratext. Furthermore, the attention of the reader is directed to the different functions of the afterword, especially as a commentary on the translator’s choices and, consequently, as an insight into the worldview inscribed into the original language. Thereby, a particular interest is paid to the translator who, in view of her literary predispositions that are clearly visible not only in the afterword, could be described as the “second author”. Finally, one of the most important issues is the very specific language used by the writer Herta Müller as she describes trivial things in an extraordinary way, using words in completely unexpected meanings and contexts. Keywords: paratexts, afterword, translation, Herta Müller, Radka Denemarková